Study on the Properties of a 2219 Aluminum Alloy Friction Stir-Welded Joint under the Biaxial Stress State - Minghao Shao; Di Wang; Cheng Huang; Xin Chang (Metals, 2023)
Friction stir welding (FSW) has been considered ideal for aluminum alloy structures. The performance of FSW joints under unidirectional stress state has been widely tested, but there is still a lack of experimental data under a biaxial stress state. For accurate characterization of the mechanical properties of 2219 aluminum alloy FSW joints under a biaxial stress state, this article conducted biaxial tests. The FSW joint was tested using scanning electron microscopy (SEM) to obtain its microscopic properties and obtain the partition results of the welded joint. The stress–strain relationship and yield characteristics of welded joints under different loading ratios were studied using biaxial tensile tests of cruciform specimens combined with digital image correlation technology. By comparing it with the existing yield criteria, the yield criterion suitable for FSW joints of 2219 aluminum alloy under a biaxial tensile load was determined.